Sociodemographic profile of preschool children with screen media dependency in urban area - Abdul Hadi, Azwanis; Abdul Latip, Nurul Akmal; Mohammad Aidid, Edre (2021)
Introduction: Screen media dependency is an addictive behaviour related to screen media use. Nowadays, the screen media is widely accessible especially in urban era. Thus, it is beneficial to identify the sociodemographic profile of children with screen media dependency. The aim of this study was to describe the sociodemographic profile of preschool children with screen media dependency in Kuala Lumpur, Malaysia. Materials and Methods: A cross sectional study was carried out among parents of preschool children aged 4 to 6 years old in Kuala Lumpur, Malaysia. The Screen Dependency Score (SDS), which is a parent report measure, was used to assess their children’s dependency to screen media. All of the children who had screen media dependency were included in this study. Results: 197 children were screened using SDS and were found out to have screen media dependency. Their mean age was 5.37 ± 0.639 years old with 50.8% were boys and 49.7% of them started using screen media ≤ 2 years old. Majority of their parents had tertiary education level (65.5%), practised restrictive type of parental mediation (56.3%) and used screen media in front of their children (94.9%). Greatest number of the children had an internet facility (91.4%), used smartphone (90.9%) and also watched television (82.2%). Majority spent 1 to 2 hours per day on screen media over the weekdays (47.7%) and ≥ 2 hours daily over the weekend (62.4%). Conclusion: Screen media dependency among preschool children may be influenced by sociodemographic factors. Thus, further analysis is needed to determine the significant association between sociodemographic factors and screen media dependency